A Qualitative Account of Children’s Perspectives and Responses to Intimate Partner Violence in Chile - Miranda, Jenniffer K. (Journal of interpersonal violence, 2021)
The literature has shown that including children’s perspectives in intimate partner violence (IPV) field research will improve our understanding of this violence and its impact on the well-being of victims. Furthermore, the literature suggests that children are not passive witnesses. Rather, they use a variety of strategies to cope with IPV. The aim of this research is to understand the experiences and coping strategies of children who have lived through IPV between their parents/caregivers. The participants of this study were nine children between the ages of 8 and 12 years (five girls and four boys). These participants were recruited from a specialized program in Chile focused on the maltreatment of children. Semi-structured interviews were conducted, and a thematic narrative analysis was used to identify recurring themes from the interviews. The results showed that children used a variety of coping strategies when an episode of violence was occurring. The aim of these coping strategies included the following: (a) emotional and behavioral self-regulation, (b) seeking social support, (c) avoiding emotional reactions related to IPV episodes, (d) escaping violent episodes, and (e) intervening to stop the IPV and protect their mothers. Along with these coping mechanisms, the results reveal that children often not only have to confront IPV when it is present in their families but are also potentially subjected to other types of victimization. The findings of this study highlight that children are active subjects with agency in response to episodes of IPV and respond through a range of actions and coping mechanisms. The researchers emphasize the relevance of integrating and validating the voices of children in research, given that children are direct victims of IPV and a high-risk group for other types of child victimization.